Childhood asthma phenotypes and endotypes: a glance into the mosaic - Francesco Foppiano; Bianca Schaub (Molecular and Cellular Pediatrics, 2023)
Abstract Background Asthma is an inflammatory lung disease that constitutes the most common noncommunicable chronic disease in childhood. Childhood asthma shows large heterogeneity regarding onset of disease, symptoms, severity, prognosis, and response to therapy. Main body Evidence suggests that this variability is due to distinct pathophysiological mechanisms, which has led to an exhaustive research effort to understand and characterize these distinct entities currently designated as “endotypes.” Initially, studies focused on identifying specific groups using clinical variables yielding different “clinical phenotypes.” In addition, the identification of specific patterns based on inflammatory cell counts and cytokine data has resulted in “inflammatory endotypes.” More recently, an increasing number of molecular data from high-throughput technology (“omics” data) have allowed to investigate more complex “molecular endotypes.” Conclusion A better definition and comprehension of childhood asthma heterogeneity is key for improving diagnosis and treatment. This review aims at summarizing the current knowledge on this topic and discusses some limitations in their application as well as recommendations for future studies.